Anishinaabe Values and Servant Leadership: A Two-Eyed Seeing Approach - McMillan, Tori (The Journal of Values-Based Leadership, 2022)
This meta-synthesis explores the connections between the Mishomis Teachings (also known as the Seven Grandfather Teachings within the Anishinaabe culture) and the principles of Servant Leadership. Through a systematic literature review of methodology and the theoretical frameworks of Two-Eyed Seeing and Ethical Space, The Mishomis Teachings and their connections to Servant Leadership are researched to answer: How is a Two-Eyed Seeing approach to Servant Leadership informed by Anishinaabe Values? The literature reveals significant connections between the Mishomis Teachings and Servant Leadership that provide an Indigenized perspective on values-based leadership practices. The implications of this study highlight a growing need within academia for Indigenous Knowledge to support and enhance Decolonization, Indigenization and Reconciliation efforts.